Diseño de un sistema de mantenimiento productivo total (TPM) para las líneas de envasado de la empresa Fuente “San Felipe” S.A. - Guamán Jacho, Gabriela Elizabeth (2021)
The source company "San Felipe S.A." has little technical documentation of the machinery, which are necessary for a maintenance system, in addition to this there is no master maintenance plan and therefore the department responsible for these activities performs corrective work, i.e. they intervene when there is a fault or failure of the machinery causing unscheduled maintenance stops and consequently affects the system productive of the company. In order to solve this problem, a Total Productive Maintenance System was carried out in order to minimize the faults and faults of the existing machinery and in this way avoid unscheduled stops. Through the research investigates the collection of technical information of the machinery of the different packaging lines is achieved, the information contained in the manufacturing manuals, as well as the experience of operators and maintenance technicians, were taken into account in determining the maintenance activities for each machine and the frequency at which they should be carried out. In addition, the company has MP9 software in which equipment and activities to be carried out are detailed. In addition, the calculation of the OEE (Global Equipment Effectiveness) was developed with the aim of measuring the effectiveness of the machinery, based on KPI's parameters achieving the increase of the OEE indicators of the production lines.